PERANCANGAN ALAT OLAHRAGA PENGHITUNG PULL UP BERBASIS MIKROKONTROLER MENGUNAKAN SENSOR ULTRASONIK - sabda sawal; aswadul fitri saiful rahman; Mayda waruni kasrani (Lembaga Penelitian Universitas Balikpapan, 2019)
The era of modernization like this technology is an important role in everyday life. The development of technological knowledge has brought people to a better era. so with the development of many people who often do research, In this study the author aims to design a microcontroller-based pull up device using ultrasonic sensors, to facilitate the pull up counter, this system consists of various electronic components such as Adruino Nano, bluetooth sensors, ultrasonic sensors, and Text Running LEDs, this tool will be operated using an Android cell phone that has been connected to Bluetooth HC-05 then press (start / stop) to turn the device on and off. The ultrasonic sensor is used to measure radio waves from sensors to objects. The results of these sensors will be displayed via LED Text Running and Android phones. One of the uses of this tool is in health sciences for the selection of TNI and POLRI admission. Perform medical tests with manual pull up calculations, longer than using a microcontroller-based pull up counter using ultrasonic sensors.